THE RELATIONSHIP OF COFFEE CONSUMPTION WITH HYPERTENSION - Florentianus Tat; Yoani Maria Vianney Bita Aty; Sabina Hamu; Elisabeth Herwanti; Aben B.Y. Romana (Jurnal Ilmiah Keperawatan, 2023)
Every year hypertension is the leading cause of death worldwide. The cause of this disease is due to modifiable factors and lifestyle. Currently, there are many people with hypertension in Kupang, ranking third out of the 10 most common diseases. The cause of kupang is the influence of lifestyle, namely consuming fatty foods such as pork, se'i (cured meat by smoking), excessive alcohol consumption, high sodium foods. Lack of exercise habits, excessive consumption of caffeine. The habit of drinking coffee is currently popular. There are many coffee shops in the city of Kupang. Coffee is a favorite drink besides alcohol. This research is quantitative with analytical descriptive design. The approach used is a cross sectional study. The number of samples is 37 people. Instrument in the form of a questionnaire. Analysis of the data used is descriptive analysis and test. The results obtained 93.3% of respondents consume packaged coffee or coffee that is processed in the factory. The habit of drinking coffee in people who suffer from hypertension is in the high category of 25 (67.6%). Most of the respondents suffer from moderate hypertension as many as 20 respondents (54.1%), mild hypertension as many as 14 (37.8%), and severe hypertension. as many as 3 respondents (8,1%). The results of the one sample t test obtained a p value of 0.00. It can be concluded that there is a significant relationship between the coffee drinking group and the incidence of hypertension. The habit of drinking coffee can cause hypertension, depending on the amount and content of caffeine consumen.